2013
DOI: 10.1039/c3nr01442h
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical composites of polyaniline–graphene nanoribbons–carbon nanotubes as electrode materials in all-solid-state supercapacitors

Abstract: A three dimensional (3D) polyaniline (PANI)-graphene nanoribbon (GNR)-carbon nanotube (CNT) composite, PANI-GNR-CNT, has been prepared via in situ polymerization of an aniline monomer on the surface of a GNR-CNT hybrid. Here, the 3D GNR-CNT hybrid has been conveniently prepared by partially unzipping the pristine multi-walled CNTs, while the residual CNTs act as "bridges" connecting different GNRs. The morphology and structure of the resulting hybrid materials have been characterized using transmission electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(87 citation statements)
references
References 44 publications
3
82
0
2
Order By: Relevance
“…Apart from PPy, PANI has also been successfully added into the graphene nanoribbon-CNT hybrid fi lms, achieving a PANI-graphene nanoribbon-CNT composite fi lm by in situ polymerization of aniline monomers on the surface of a graphene nanoribbon-CNT hybrid fi lm. [ 175 ] Nanocarbon-based materials often show good stability, but their capacitance is relatively low since not all their BET surface area can be electrochemically accessible. Accordingly, various conductive polymer nanostructure materials such as PANI, PPy, and PEDOT have been assembled into the nanocarbon architectures, forming fl exible composite materials.…”
Section: Graphene/cnts/conductive Polymer Composite Architecturesmentioning
confidence: 99%
“…Apart from PPy, PANI has also been successfully added into the graphene nanoribbon-CNT hybrid fi lms, achieving a PANI-graphene nanoribbon-CNT composite fi lm by in situ polymerization of aniline monomers on the surface of a graphene nanoribbon-CNT hybrid fi lm. [ 175 ] Nanocarbon-based materials often show good stability, but their capacitance is relatively low since not all their BET surface area can be electrochemically accessible. Accordingly, various conductive polymer nanostructure materials such as PANI, PPy, and PEDOT have been assembled into the nanocarbon architectures, forming fl exible composite materials.…”
Section: Graphene/cnts/conductive Polymer Composite Architecturesmentioning
confidence: 99%
“…These make GNRs ideal candidates for advanced electrochemical and electronic devices in many fields, such as lithium ion batteries (Lin et al, 2013a), supercapacitors (Lin et al, 2013b;Liu et al, 2013), organic photovoltaics (Osella et al, 2012), large-scale device fabrication (Martin-Fernandez et al, 2012), high dielectric constant gate dielectrics (Liao et al, 2010), sensors Sun et al, 2011) and optoelectronics (Wei et al, 2013). Recent researches (Wei et al, 2013;Yang et al, 2013) confirmed that the CNTs-GNRs composites could exhibit much more excellent electrochemical performance compared with a single component of CNTs or GNRs due to the synergistic effects:…”
Section: Introductionmentioning
confidence: 92%
“…[123] Tuning the chemical polymerization process achieved hierarchical nanostructures with high specific area on individual CNTs. (Figure 11 capacitance.…”
Section: Inorganic Pseudocapacitive Materialsmentioning
confidence: 99%